2011
DOI: 10.1111/j.1475-4754.2011.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Shaft‐hole Axes From Caput Adriae Made From Amphibole‐rich Metabasites: Evidence of Connections Between Northeastern Italy and Central Europe During the Fifth Millennium Bc

Abstract: Here we show the results of a study concerning a small group of shaft‐hole axes found in northeastern Italy, made from amphibole‐rich metabasites, fine‐grained and free of phenoblasts. The main mineral phases are amphibole, ranging from actinolite to hornblende, and plagioclase (An10–15 and An70–77). The amphiboles generally show a needle shape and are often radially arranged. Quartz is present in thin veinlets, while ilmenite is widespread in small patches. The petrographic and geochemical features suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…The morphological features and recent archaeometric studies concerning the polished stone axe found near Castions di Strada testify long-distance connection systems covering all Central Europe and dating back to the 5th millennium BC (Bernardini et al 2012). tudia niversitatis an update on the data about the late neolithic and eneolithic in fr iuli of pierced axes have been found (Corazza et al 2006), the castelliere of Gradisca sul Cosa, and most of all the already described castelliere of Meduno-Sach di Sotto (Visentini et al 2015).…”
mentioning
confidence: 63%
“…The morphological features and recent archaeometric studies concerning the polished stone axe found near Castions di Strada testify long-distance connection systems covering all Central Europe and dating back to the 5th millennium BC (Bernardini et al 2012). tudia niversitatis an update on the data about the late neolithic and eneolithic in fr iuli of pierced axes have been found (Corazza et al 2006), the castelliere of Gradisca sul Cosa, and most of all the already described castelliere of Meduno-Sach di Sotto (Visentini et al 2015).…”
mentioning
confidence: 63%
“…2d) or with an elongated triangular shape and a rounded butt (Fig. 2c), are much more common in Friuli-Venezia Giulia region, in NE Italy, and Slovenia: D'Amico et al 1996;Bernardini 2007Bernardini -2008Bernardini et al 2011Bernardini et al , 2012Bernardini et al , 2014Schmid 1910;Koršec and Koršec 1969;Lubšina-Tušek 1993;Velušček 2004) and resulted to be manufactured from various metamorphic rock, in particular serpentinites and volcanics. Contacts and consequent circulation of these models in the trans-Adriatic area appear evident from the second half of the 4th millennium BC (Cazzella 2003).…”
Section: Perforated Axe-hammersmentioning
confidence: 95%
“…); and a metabasite sample (NB01) from the southern thermal aureole of Tanvald granite in northern Bohemia (Bernardini et al . ).…”
Section: Geochemistrymentioning
confidence: 97%
“…Recent papers have discussed the provenance of the metadolerite, serpentinite and metabasite shaft‐hole axes found in the Caput Adriae (north‐eastern Italy, western Slovenia and north‐western Croatia), making a contribution to the understanding of the technological and cultural changes that occurred during Neolithic and the Copper Age in this part of Europe (Bernardini et al . ). To complete the study of these artefacts, a group informally called ‘metaultramafite axes’ (Peloi 1996–7; D'Amico et al .…”
Section: Introductionmentioning
confidence: 97%